RASIONALITAS MASYARAKAT, DALAM TRADISI MAELO JALUR DI DESA SUNGAI PINANG KECAMATAN HULU KUANTAN KABUPATEN - ", Sepriadi; Hidir, Achmad (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
This study examines the Rationality of Society in Tradition of Maelo Jalur on Sungai Pinang, Hulu Kuantan Sub-district, Kuantan Singingi District. Maelo Jalur is a Tradition take the wod for jalur from the forest to the village by using human power as well as using tools and certain rituals that must be performed. Maelo jalur is a culture that is still maintained  and awaited  by society of Kuantan Singingi, because every jalur must carry out the traditions of the Maelo Jalur. Nowadays Maelo Jalur has undergone a change and the society has thought rationally so that the jalur can quickly arrive. In this study, researchers used rational choice theory from James Coleman. This research method is descriptive qualitative with 5 informants consisting of village heads, leaders of jalur, hamlet heads, jalur shaman and Sungai Pinang village youth. The results of this study indicate that in the present era of Maelo Jalur tradition changes both the way, the energy used, the time, and the costs in Maelo Jalur, this is due to the depelopment of the era, education and the mindset of a more rational society. Maelo Jalur is a unifying tool for the village and generates values of mutual cooperation. It is hoped that resources and norms can be maintainted in the tradition of Maelo Jalur.  Keyword: Maelo Jalur, Rationality, Tradition.